Fascisme et République - Olivier Forlin (Laboratoire Italien)
In the early years of the fascist movement, a lot of its activists were attached to the Republican ideals. But, with the aim to take legally the power, Mussolini compromised with monarchy. Then, in spite of the reduction of the King’s power, the monarchy and the Statuto remained in function until July 1943. It was only within the RSI, political regime without a real autonomy, that fascism was able to build a republican regime. However, from an ideological point of view, a part of fascist activists were acting in the legacy of Jacobinism and Republican and Revolutionary movements of the nineteen century. Invoking Mazzini’s thought, they inspired the totalitarian trend of fascism which finally meant the republican regime advent.